INCIDENCE OF VATKANTAKA IN PES PLANUS INDIVIDUALS-AN OBSERVSTIONAL STUDY - Prakash Adhav, Ketki; Lahare, Kunal H.; V Shekokar, Anantkumar; Adhav, Prakash (International Journal of Ayurveda and Pharma Research, 2015)
This study is helpful for Ayurvedic as well as Modern physicians to understand concepts related with Vishampada Rachana and Vatkantaka and thus contribute in the treatment of Vatkantaka The aim of study is to observe the structural changes in Vatkantaka in the Pes Planus patients. The objective of this study is to establish relation between Vatkantaka and Pes Planus. Study also helps to analyze common incidence of Vatkantaka in patients of Pes Planus. Observational study was conducted in 30 diagnosed patients of Vatkantaka with pes planus by using a well designed case record form, both feet prints, radiograph of both feet with ankle joint (lateral view), Goniometry. Data thus generated was neatly arranged and assessed statistically for results and represented. Discussions regarding structural changes observed in study were discussed with experts in Ayurveda & modern medicine. The findings of study are significantly useful for physicians in understanding the important structural causes in Vatkantaka.The study shows six different diagnoses of 30 patients out of which 5 i.e. 16.66% of Plantar fascitis, 5 i.e.16.66% of Ankle sprain, 14 i.e. 46.66% of Calcaneal spur with plantar fascitis, 1 i.e. 3.33% of Metatarsalgia, 4 i.e. 13.33% of Corn. 1 i.e. 3.33% of Claw toe with corn. (Table no.2).Hence above findings shows that Vatkantaka is more nearer to Calcaneal spur with plantar fascitis.Thus from above discussion, we can say that there is a inter-relation between Vatkantaka and Pes Planus in many things like diagnosis, causes, nature of pain, joint movements, joints and their axis,  marmasthana and ultimately study shows common occurrence of Vatkantaka in Pes Planus.